Molecular dynamics study of structural properties of γ-aminobutyric acid (GABA) (BIBECHANA, 2021)
The study of the structural conformation of Gamma-aminobutyric acid (GABA) exhibits its biological and chemical activities. The GABA molecule is responsible for neurotransmission from one neuron to another neuron and activates the ion channels to pass the chlorine and sodium ions in nerve cells. Its conformation in the solid-state and gas state are extremely different and it also shows five different conformations in an aqueous solution. The study of its structure in such an environment can reveal its activity in the cellular environment. We have performed the classical molecular dynamics study of this system of GABA in the aqueous medium to deal with its structure. Radial distribution function (RDF) has been used to study the structural properties of the system.BIBECHANA 18 (1) (2021) 67-74